Handbok för Ex-klassning - Karlsson, Johan; Brandt, Jonas (My University, 2014)
Hazardous area classification is applied in areas where an explosive atmosphere can occur and adjacent areas. An explosive atmosphere is defined by a mixture of gas or steam in air with a concentration such that it can be ignited. This concentration varies for different substances and is counted in volume percentage. If an area is hazardous or not depends on how often an explosive atmosphere occurs. This also gives the area a zone classification, zone 0, 1 or 2, where zone 0 is the one where an explosive atmosphere occurs most frequently. There are different ways to prevent an explosion; one way is to eliminate the contact between air and the flammable substance or limit the amount of oxygen, to make it impossible for the substance to ignite. Another way is to change the substance to a less flammable substance, this is called substitution. A third way to prevent an explosion is using hazardous area classified equipment. The equipment can be provided with many different protection techniques depending on what is needed to have protection against. Protection may be needed against dust, sparks and arcs, energy levels, evacuating or penetrating gases, surface temperature and static electricity. One common factor is to design equipment that does not generate energy higher than the minimum ignition energy for the managed flammable substance which is often very low. For the construction of an industrial plant is the division of risk zones done by specially educated personnel. How this is done depends entirely on the requirements from the ATEX directive. A document shall be issued where all the collected information shall be involved, such as classification plan, zone drawings, maintenance and technical data. This literature study has led to a documentation of the basic theory of the ex-classification ashore and on ships. The thesis is mainly directed to technicians or engineers who work in operation engineering.
Keywords: Annan teknik; Transport; Other Engineering and Technologies; Transport